PENERAPAN TERAPI GESTALT DALAM PENGELOLAAN EMOSIONAL YANG TERPENDAM PASIEN SKIZOFRENIA PARANOID “SW” DI RUMAH SAKIT JIWA Dr. H. MARZOEKI MAHDI KOTA BOGOR - Rajabi, Muhammad Ibadillah; Utami, Nazera nur (Sekolah Tinggi Keguruan dan Ilmu Pendidikan (STKIP) Melawi, 2025)
Schizophrenia based on DSM-V defines it as a mental disorder characterized by psychotic symptoms that last for at least six months. Where reality and thought patterns cannot be in line. This community service aims to explore the application of gestalt therapy using the Nourisment Technique in emotional management in client